2012
DOI: 10.1128/mbio.00137-12
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Human Parainfluenza Virus to Airway Epithelium Reveals Fusion Properties Required for Growth in Host Tissue

Abstract: Paramyxoviruses, a family of RNA enveloped viruses that includes human parainfluenza virus type 3 (HPIV3), cause the majority of childhood croup, bronchiolitis, and pneumonia worldwide. Infection starts with host cell receptor binding and fusion of the viral envelope with the cell membrane at the cell surface. The fusion process requires interaction of the two viral surface glycoproteins, the hemagglutinin-neuraminidase (HN) and the fusion protein (F). We have previously shown that viruses with an HN/F pair th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 31 publications
4
86
0
Order By: Relevance
“…The HPIV3 HAEadapted strain and the CI-1 strain attain viral titers of up to 10 7 and 10 8 PFU/ml, respectively, in HAE, and greater than 10 5 PFU/g of lung tissue in cotton rats compared to those of the HPIV3 laboratory reference strain, which we previously found to peak at 10 5 PFU/ml in HAE and 10 4 PFU/g of lung tissue in cotton rats (20). Viruses collected from HAE infected with the HAE-adapted HPIV3 produced small plaques (average diameter of 0.1 mm) relative to those of the reference strain (average diameter of 0.6 mm) (19), and the CI-1 virus produced plaques similar in size to those of the HAE-adapted strain (data not shown). CI-1 HN/F, like the HAE-adapted strain HN/F, fuses cultured cells little or not at all.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The HPIV3 HAEadapted strain and the CI-1 strain attain viral titers of up to 10 7 and 10 8 PFU/ml, respectively, in HAE, and greater than 10 5 PFU/g of lung tissue in cotton rats compared to those of the HPIV3 laboratory reference strain, which we previously found to peak at 10 5 PFU/ml in HAE and 10 4 PFU/g of lung tissue in cotton rats (20). Viruses collected from HAE infected with the HAE-adapted HPIV3 produced small plaques (average diameter of 0.1 mm) relative to those of the reference strain (average diameter of 0.6 mm) (19), and the CI-1 virus produced plaques similar in size to those of the HAE-adapted strain (data not shown). CI-1 HN/F, like the HAE-adapted strain HN/F, fuses cultured cells little or not at all.…”
Section: Resultsmentioning
confidence: 99%
“…None of the strains with proficient fusion activities that grow efficiently in cultured monolayer cells succeed in vivo. We observed that the HPIV3 CI-1 collected directly from a patient grew efficiently in cotton rats, producing 2 to 3 logs more virus than the laboratory reference strain at the peak of infection, similarly to the HAE-adapted strain, which we had previously found to be viable in vivo (19,20).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…These cells express basal cell markers including cytokeratin 5 and the transcription factor p63 (Hackett et al, 2011a) and have been used as models of basal cells. al., 2010), mucociliary transport (Seagrave et al, 2012), airway toxicology (Mathis et al, 2013;Watson et al, 2010), electrophysiology (Hirsh et al, 2008), and bacterial and viral infection studies (Deng et al, 2014;Mitchell et al, 2011;Palmer et al, 2012;Ren and Daines, 2011;Ren et al, 2012). The MucilAir cultures have been characterized electrophysiologically and are fully functional: the activity of the main epithelial ionic channels, such as CFTR, EnaC, Na/K ATPase, etc.…”
Section: Primary Lung Cellsmentioning
confidence: 99%